Multicultural Value Analysis of Social Sciences Study Primary School - Susianti, Oni Marliana; Setyowati, Dewi Liesnoor; Atmaja, Hamdan Tri (Journal of Primary Education, 2019)
This study aims: (1) to analyze the implementation of multicultural values ​​in social sciences subjects; (2) to determine the supporting and inhibiting factors of multicultural value education in social sciences subjects; (3) to nalyzing the application impact of multicultural values ​​in student behavior. The method in this study was a qualitative approach also called naturalistic and sample selection using purposive sampling and snowball techniques. The results of the study show that: (1) the implementation of multicultural values ​​could be seen in the process of social sciences learning by giving the motivation to accept and appreciate diversity and to do habituation such as holding deliberations, forming heterogeneous groups, and direct reprimands; (2) factors supporting the implementation of multicultural values ​​through school habituation such as lab fire activities, Kartini day commemoration, special services, and 15 minutes of reflection, planting values ​​in the family arena as well as various school and family arena conditions. The inhibiting factor is in the 2013 curriculum material that is less profound and there are several repetitions of material that are not needed; (3) the application of multicultural values ​​could be seen in students' behavior namely respecting and accepting religious, ethnic, ethnic and cultural diversity, not interfering with each other, respecting friends who have different opinions, making friends with anyone without seeing differences in religion, ethnicity, and ethnicity, not hostile to each other, admiring  Indonesia culture, has a desire to preserve culture and wear traditional clothing for cultural activities held by school.